Serial Mediators of Memory Support Strategies Used With Cognitive Therapy for Depression: Improving Outcomes Through Patient Adherence and Treatment Skills. Issue 1 (January 2023) - Sarfan, Laurel D.; Zieve, Garret G.; Mujir, Firdows; Gumport, Nicole B.; Xiong, Mo; Harvey, Allison G.
Highlights: Present study tested serial mediators of memory support strategies used in treatment. Participants were adults with major depressive disorder receiving Cognitive Therapy. Depression severity and global impairment were evaluated as outcomes. Adherence and utilization/competence of treatment skills serially mediated outcomes. Memory support strategies may boost important treatment mechanisms and outcomes. Abstract: Patient memory for treatment is poor. Memory support strategies can be integrated within evidence-based psychological treatments to improve patient memory for treatment, and thereby enhance patient outcomes. The present study evaluated possible mechanisms of these memory support strategies. Specifically, we tested whether therapist use of memory support strategies indirectly predicts improved patient outcomes via serial improvements in (a) patient adherence throughout treatment and (b) patient utilization and competency of treatment skills. Adults with major depressive disorder ( N  = 178, mean age = 37.93, 63% female, 17% Hispanic or Latino) were randomized to Cognitive Therapy plus a Memory Support Intervention or Cognitive Therapy-as-usual. Because therapists from both treatment groups used memory support strategies, data from conditions were combined. Blind assessments of depression severity and overall impairment were conducted before treatment, immediately posttreatment (POST), at 6-month follow-up (6FU), and at 12-month follow-up (12FU). Patient adherence to treatment was rated by therapists and averaged across treatment sessions. Patients completed measures of treatment mechanisms—namely, utilization and competency in cognitive therapy skills—at POST, 6FU, and 12FU. Results of serial mediation models indicated that more therapist use of memory support predicted lower depression severity at POST, 6FU, and 12FU indirectly and sequentially through (a) increased patient adherence during treatment and (b) more utilization and competency of Cognitive Therapy skills at POST, 6FU, and 12FU. The same patterns were found for serial mediation models predicting lower overall impairment at POST, 6FU, and 12FU. Together, boosting memory for treatment may represent a promising means to enhance pantreatment mechanisms (i.e., adherence and treatment skills) as well as patient outcomes.